Effects of white noise auditory stimulus on stability and balance in sit-to-stand and standing motion of chronic stroke patients - Hee-sung Lim; Sang-heon Park; Joo-Nyeon Kim (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to investigate the effect of auditory stimulus using white noise on stability and balance during sit-to-stand and standing tasks of chronic stroke patients. Methods Eighteen chronic stroke patients participated in this study. They asked to perform the tasks of sit-to-stand, standing with eyes open and standing with eyes closed before and after listening to white noise. Eight infrared cameras and one force plate were used to evaluate the stability and balance before and after the white noise stimulus during each task. Results There was no significant difference between before and after white noise stimulus in all tasks. On the other hand, the anteroposterior range of CoP was significantly decreased after white noise stimulus in standing with eyes-closed (p<.05), and the sagittal angle of CoP-CoM was significantly decreased after white noise stimulus in standing with eyes-open and eyes-closed (p<.05). Conclusion Auditory stimulus using white noise improves the balance of chronic stroke patients. Therefore it is thought to be helpful for the independent daily life of chronic stroke patients.